Sigmoid colonic perforation by foreign body rectum: A case report - Deshpande, S K; Varshney, Amar (Indian Journal of Case Reports, 2020)
Rectal foreign bodies are infrequently encountered in surgical practice and present perplexing management situations. They can be dealt with in varied manners depending on their size, location, presentation, and expertise available. Surgery with a laparotomy is usually reserved for patients with perforation or ischemic bowel or cases of failed transanal attempts. Patients with perforation who present early, having minimal or no peritoneal contamination can be managed with primary repair and peritoneal lavage. We report a case of rectosigmoid foreign body presenting as an acute abdomen in elderly patient necessitating emergency laparotomy.